A Study On The Communication And Emphatic Skills Of The Students Having Education On Tourism Sector - M.erhan Summak (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
Communication is of great importance for the people to express themselves and maintain their lives. Thoughts and views should be transferred to others in tourism industry in which people interaction is rich, and it is only by this way possible to get along with others. It can be said that communication has a function to connect the parties. If the communication is insufficient, it means that some problems may arose while servicing. This situation results in both dissatisfaction of the customers and a decrease in the service standard of the firm. For this reason, communication barriers should be eliminated. An efficient management in businesses relies on an effective communication process. The views and the decisions of the management should be transferred in a way that contains mutual feelings and gestures of both sender and receiver. So, communication forms the basis of organizational activities. Moreover, in order to mention about the communication, there should be a relationship between the individuals that requires the mutual exchange of thoughts, views and knowledge among them. Tourism enterprises are well established on the human relations and are well known with their characteristics of labor intensively and communication insensitivity. Some of the problems in tourism industry which is important regarding to the face to face communication both in guest level and managerial level arise from the lack of direct and inefficient communication. However, direct communication prevents the enterprises from the problems caused by misunderstanding and hear saying. It might be said that industrial staff who has efficient communication skills could handle the problems both arising inside the enterprise or arising from the tourists efficiently. Additionally, skilled personnel about efficient communication and empathy might think and behave more problem focused and objective. Due to the relative importance of this subject, this study is focused on the tourism education students that are thought as prospective workers for tourism industry. Data gathered from 300 hundred students who are being educated in various tourism departments at Selcuk University are classified, processed and evaluated by means of statistical software SPSS for Windows 17.0